2022
DOI: 10.3390/ijerph192013697
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Crisis Management and Post-Traumatic Growth among Chinese Preschool Teachers during COVID-19: Risk Perception as a Moderator

Abstract: This study explored post-traumatic growth among preschool teachers during COVID-19 and investigated associations among post-traumatic growth, perceived crisis management, and risk perception. The participants were 2921 Chinese preschool teachers (96.5% women). Teachers’ reports of post-traumatic growth, perceived crisis management, and risk perception were analyzed by multivariate techniques. The results revealed that preschool teachers’ post-traumatic growth was at an intermediate level, and there was no sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Religious/Spiritual Change: the stressful event encourages the individuals to reflect on existential questions and become more aware of life's uncertain and constantly changing nature [22]. Studies that examined post-traumatic growth among teachers and school principals during the pandemic found that social support and positive or adaptive coping strategies [25,26] are positively associated with post-traumatic growth [27,28]. Furthermore, teachers who regulated their emotions effectively reported higher post-traumatic growth [28].…”
Section: Theoretical Model: Post-traumatic Growthmentioning
confidence: 99%
“…Religious/Spiritual Change: the stressful event encourages the individuals to reflect on existential questions and become more aware of life's uncertain and constantly changing nature [22]. Studies that examined post-traumatic growth among teachers and school principals during the pandemic found that social support and positive or adaptive coping strategies [25,26] are positively associated with post-traumatic growth [27,28]. Furthermore, teachers who regulated their emotions effectively reported higher post-traumatic growth [28].…”
Section: Theoretical Model: Post-traumatic Growthmentioning
confidence: 99%
“…Nevertheless, the turnover rate of kindergarten teachers remains considerably elevated, particularly within East Asian societies [1]. The COVID-19 pandemic has had a detrimental effect on the remuneration of these educators, leading to a notable surge in resignations and career changes within the kindergarten teaching sector [2]. Within four months after the outbreak of the epidemic, the turnover rate of kindergarten teachers in China was 19.4% [3], far exceeding the annual turnover rate of teachers in Finland, Singapore and other places of about 4%, and also exceeding the annual turnover rate of preschool and early childhood care teachers in the United States of 15% [4].…”
Section: Introductionmentioning
confidence: 99%
“…Within four months after the outbreak of the epidemic, the turnover rate of kindergarten teachers in China was 19.4% [3], far exceeding the annual turnover rate of teachers in Finland, Singapore and other places of about 4%, and also exceeding the annual turnover rate of preschool and early childhood care teachers in the United States of 15% [4]. The high turnover rate of kindergarten teachers in China has hindered the smooth implementation of various kindergarten work during the epidemic period, which has aroused the concern of the education community about the low stability of kindergarten teachers [2,3,5]. The considerable rate of turnover observed among kindergarten teachers serves as a crucial obstacle to the progress of early childhood education in China, as indicated by recent research [5][6][7].…”
Section: Introductionmentioning
confidence: 99%